Family Migration and Education Mobility. Pathways to Success in Autobiographies of Moroccan-Origin Girls - Mariagrazia Santagati (Journal of Mediterranean Knowledge, 2020)
The article proposes an in-depth analysis of the link between family migration and educational mobility, using data deriving from an original qualitative research on successful students with an immigrant background. First of all, a conceptual framework is provided, identifying some crucial theoretical and empirical issues concerning migrant families: educational mobility as a family strategy and project; the challenges of intergenerational transmission in revisiting cultural and ethnic identities; the importance of the “act of passing on” trough family relations. Secondly, autobiographies of immigrant-origin students are used to examine whether and in which conditions family functions as a driver of educational success. Through the biographical approach, strategies and narratives students adopt to represent family migration and the relationships with parents are reconstructed. Finally, using the outlined conceptual frame, the emblematic stories of Amna, Ikram, and Sole, three girls with Moroccan origin, are analyzed, illustrating different ways to negotiate values, norms, behaviors, and to reshape family identities and ties, towards a common goal of educational success.